Factores de riesgo de conducta suicida en adultos mayores - Latorre Guaman, Heidy Carolina (2023)
ABSTRACT: Every suicide is a tragedy that has a significant impact on families, communities, and society as a whole. Suicide is a serious public health problem that is often ignored. The present investigation aimed to determine the main psychological factors and suicidal behavior in older adults. A bibliographic review was carried out with a quantitative approach; the population was constituted of 16,100 documents from which, based on inclusion criteria, 40 scientific articles were chosen by convenience sampling, the literature review matrix was used, articles with the Average Count Citation (ACC) formula greater than 1. The main psychological risk factors associated with suicidal behavior in older adults were identified as multi-causal and primarily due to social, family, medical, psychiatric, neurological, and biological consequences. The most common characteristics of older adults with self-intentions are mild to severe cognitive impairment, The most common characteristics of older adults with suicidal intentions are mild to severe cognitive impairment, independent adults in loneliness, smoking as a toxic habit, and hypertension as a chronic and contagious disease, in addition to depression and anxiety and, as an aggravating factor, alcoholism